2012
DOI: 10.1155/2012/823970
|View full text |Cite
|
Sign up to set email alerts
|

Anurans as Intermediate and Paratenic Hosts of Helminth Infections in the Rainforest and Derived Savanna Biotopes of Southern Nigeria

Abstract: Anurans from the rainforest (Okomu National Park) and derived savanna (Agbede) locations in Nigeria were investigated for their role either as intermediate or paratenic hosts of helminth infections. A total of 269 anuran specimens (157 from the Okomu National Park and 112 from Agbede) were examined. Metacercariae of a strigeoid trematode, two nematode species, a proteocephalid cestode, and an acanthocephalan were recovered from infected hosts. Except for the strigeoid trematode, which was only recorded in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 22 publications
3
20
1
Order By: Relevance
“…in Nigeria is the lizard Agama agama reported by Adeoye and Ogunbanwo (2007). As already reported by Imasuen et al (2012b), the larval ascaridida found in this study, whether in the body cavity or in the stomach mucosa, most probably use the infected anurans as transport hosts.…”
Section: Discussionsupporting
confidence: 86%
“…in Nigeria is the lizard Agama agama reported by Adeoye and Ogunbanwo (2007). As already reported by Imasuen et al (2012b), the larval ascaridida found in this study, whether in the body cavity or in the stomach mucosa, most probably use the infected anurans as transport hosts.…”
Section: Discussionsupporting
confidence: 86%
“…Examination of anurans from a monoculture plantation (Oil Palm) and those collected from a derived savannah location has revealed that anurans in these locations also habour strigeiod trematode larvae. Some of the larvae recovered were encysted like those reported by Imasuen et al (2012) while others were recovered unencysted in the body cavity and lungs, respectively. In this paper, we report the different strigeoid trematode larvae infecting anurans collected from a monoculture plantation located in a rainforest environment and a derived savannah location in southern Nigeria.…”
Section: Introductionsupporting
confidence: 59%
“…The anurans (tree frogs) examined for strigeoid trematode larvae at the Okomu National Park as reported by Imasuen et al (2012) are shown in Table 1. In this location, six tree frogs (Afrixalus dorsalis, Afrixalus cog.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations